Evaluation of sour cherry varieties grown with environmental technology - Felföldi, J.; Szabó, T.; Nyéki, J.; Szabó, Z.; Soltész, M.; Apáti, F. (International Journal of Horticultural Science, 2010)
The evaluation of a produce is an important moment of predicting its success on the market. The general impression, which is decisive, when a consumer chooses to purchase the commodity, should be interpreted in more objective, measurable terms. Primary data have been collected on fresh fruits derived from different growing technologies by organoleptic tests and the data filled up in the forms are processed with correlation analysis. The components were: taste, aroma, flesh firmness. The coefficients of correlation showed that the rest of characters as the appearance, juiciness, and the sugar/acid ratio.